2014
DOI: 10.1515/prilozi-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

Histological Structure of the Thyroid Gland in Apolipoprotein E Deficient Female Mice After Levothyroxine Application

Abstract: The aim of this study was to determine the histological characteristics of the thyroid gland in ApoE KO-/- mice following the application of levothyroxine (l-thyroxine).A total of 12 female ApoE KO-/- mice were divided into two groups. A control group of mice received distilled water and the experimental group received l-thyroxine dissolved in drinking water at a daily dose of 2 µg/ml, over 12 weeks. The paraffin sections were processed with the usual haematoxilin-eosin technique of staining.Qualitative histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The follicular cells are columnar while the follicles are active. The follicular cells are cuboidal epithelium in their normal state (Petrova et al, 2014). But it is also possible for several cells within the same thyroid tissue to exhibit varying degrees of activity (Khan & Farhana, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The follicular cells are columnar while the follicles are active. The follicular cells are cuboidal epithelium in their normal state (Petrova et al, 2014). But it is also possible for several cells within the same thyroid tissue to exhibit varying degrees of activity (Khan & Farhana, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, the thyroid gland in rodents is similar to that of humans, except the difference in size of the follicles that are comparatively small and are surrounded by the cuboidal epithelium [27,28]. Petrova et al 2014 demonstrated that the administration of l-thyroxine or availability of thyroid hormones is characterized by the presence of large size follicles, availability of more colloid, reduction in resorptive vacuoles with flattened follicular epithelium as it is evident from the images of normal (NOR+VEH), and the group administered with CN 600 mg/kg, where no or less vacuolization was present and follicular size was large with flattened cuboidal epithelium, colloidal appearance in follicles, slightly variable in size, parafollicular cells, or C-cells in between the follicles, fenestrated capillaries with visible appearance of interlobular connective tissue [29]. Ali Rajab et al 2015 demonstrated that the supranormal levels of thyroid hormones or conditions resembling hyperthyroidism distort the morphology of the gland characterized by distention of lumen of follicles, reduction in thyrocyte height, follicular remodeling (fusion), and thyrocyte death due to lack of trophic effect and cytoprotection offered by TSH [30].…”
Section: Kaur and Vermamentioning
confidence: 94%